The Impact of Overlooking the Social Dimension in Urban Projects on Citizens’ Behavior Toward Public Property: A Case Study of Kenitra City - EL Mestari, Mohamed; Tayii, Mbarek (Journal of Humanities & Social Sciences, 2025)
This study aims to analyze the impact of overlooking the social dimension in urban projects on citizens’ behavior toward public property, using the city of Kenitra as a case study. The research adopts a mixed sociological approach, combining both quantitative and qualitative tools—including surveys, interviews, and case studies—to develop a comprehensive and in-depth understanding of the phenomenon. The findings reveal a direct causal relationship between the exclusion of the social dimension in the planning and implementation of urban projects and the emergence of negative behaviors such as neglect and vandalism. These behaviors are attributed to a weakened sense of spatial belonging, feelings of social exclusion, and a decline in trust in institutions. The study recommends integrating the social dimension as a central component at all stages of urban project development, through active citizen participation in decision-making and the reinforcement of community engagement mechanisms. Such integration is essential to ensuring the sustainability of urban projects and mitigating destructive behaviors toward public property.
Keywords: social dimension; urban planning; urban projects; public property; community participation; spatial belonging; vandalism; sustainability